Exploring the ummatic personality dimensions from the psycho-spiritual paradigm - Othman, Nooraini (Canadian Center of Science and Education, 2011)
The Ummatic Personality Inventory was devised within a specific framework. It intends to be an assessment tool for self-introspection (muhasabah) and self-improvement (islah). Central to this idea is the concept that one would be able to identify the area where improvements could be made as far as one’s personality as a Muslim is concerned. This research was conducted at the International Islamic University Malaysia (IIUM), Gombak, Selangor, and Universiti Teknologi Malaysia (UTM), Skudai, Johor. The sample size was 588. An advanced statistical method, Principal Component Analysis (PCA), was used. PCA was used to identify the underlying dimensions for each construct of the instrument. The results provide evidence that the developed instrument possesses sound psychometric properties. The reliability test indicated that the instrument was reliable, given that the overall reliability value of Cronbach’s Alpha was .963. The findings revealed that with the use of PCA, the Ibadah construct produced 5 significant factors, the Amanah construct generated 5 factors and the Ilm construct produced 2 factors. In conclusion, this study produced a prototype of the Ummatic Personality Inventory that possesses sound psychometric properties and contributes to the development of a novel psychological instrument from the Islamic perspective.